Remarks on the Historic-geographic Method and Structuralism in Folklore Studies: the Puzzle of Chain Letters - Elo-Hanna Seljamaa (Journal of Ethnology and Folkloristics)
Structuralism in folklore studies was in many ways a reaction against the previous scholarship and the historic-geographic method in particular. In this paper the relationship between the two is analysed through a comparison between Walter Anderson’s historic-geographic and Alan Dundes’ structuralist treatment of chain letters. Anderson published his article on types of Estonian chain letters in 1937, whereas Dundes dealt with chain letters repeatedly in the 1960–70s. Drawing on T. Kuhn’s concept of paradigm as a “way of seeing the world”, the article examines the concept of folklore and folklore studies proposed by either scholar in his discussion of chain letters and seeks to interpret his reasons for taking interest in such a phenomenon. It argues that rather than being incommensurable, the historic-geographic method and structuralism as represented by Anderson and Dundes share an understanding of folklore as a collection of classifiable single items characterised by simultaneous variation and stability.